Pengaruh Arus Kas Operasi, Ukuran Perusahaan Terhadap Tax Avoidance pada Perusahaan Barang Konsumsi yang Terdaftar di BEI Periode 2019-2021: Indonesia - Aryanti, Ega Kirana Aryanti; Handayani, Rini (Jurnal Ilmiah Wahana Akuntansi, 2023)
The purpose of this study is to examine the effect of operating cash flow and company size on tax avoidance practices in consumer goods sector companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2021 period. This study uses a quantitative method with secondary data in the form of company financial reports. This type of research is causal explanatory. The population of this study consisted of 83 companies. The sector was selected through a purposive sampling technique, resulting in 32 companies. The data analysis was carried out using multiple regression tests. The research results show that operating cash flow has a significant negative effect on tax avoidance practices. Meanwhile, company size has no significant effect on tax avoidance practices.